David levy's guide to eclipses, transits and occultations - Levy, David H. (Cambridge, Cambridge University Press, 2010)
In this simple guide, David Levy inspires readers to experience the wonder of eclipses and other transient astronomical events for themselves. Covering both solar and lunar eclipses, he gives step-by-step instructions on how to observe and photograph eclipses. As well as explaining the science behind eclipses, the book also gives their historical background, discussing how they were observed in the past and what we have learned from them. This personal account contains examples from the 77 eclipses the author has witnessed himself. The guide also includes chapters on occultations of stars and planets by the Moon and of asteroids by stars, and the transits of Mercury and Venus. Tables of future eclipses make this invaluable for anyone, from beginners to practised observers, wanting to learn more about these fascinating events.
Index 175-177p.
Keywords: Astronomy; Eclipse; Occulatations; Transits; Physics